Creative Construction Conference 2018 - Proceedings 2018
DOI: 10.3311/ccc2018-044
|View full text |Cite
|
Sign up to set email alerts
|

Best Value Procurement – The first experiences from Norway

Abstract: Best Value Procurement (BVP) is a method for contractor selection and project management, which seeks to increase project value by emphasizing the competence and expertise of the contractor. Several studies in the US and Netherlands indicate promising results. The method is new to Norway and pilot projects in the construction industry are testing the method. Limited research has been done to explore the experiences of these pilot projects. This study investigates how BVP was implemented in practice and the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The case study results are shown in Table 2 and Table 3. Both tables follow the framework earlier described and published by Högnason et al (2018) and Storteboom et al (2017). Table 2 shows that BVP was practiced quite similar in the two projects, and mostly as described by van de Rijt et al (2016).…”
Section: Findings and Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The case study results are shown in Table 2 and Table 3. Both tables follow the framework earlier described and published by Högnason et al (2018) and Storteboom et al (2017). Table 2 shows that BVP was practiced quite similar in the two projects, and mostly as described by van de Rijt et al (2016).…”
Section: Findings and Discussionmentioning
confidence: 53%
“…The main reference on how BVP should be implemented is the book written by the originator of the approach -Dean Kashiwagi (Kashiwagi, 2016). However, in the European context, the approach is adapted to fulfil EU public procurement legislation requirements (Högnason et al 2018). This approach has been used on several Dutch projects and is the approach that Norwegian projects are based upon (van de Rijt et al 2016).…”
Section: Best Value Procurementmentioning
confidence: 99%
See 2 more Smart Citations
“…This philosophy encourages transparency and simplicity throughout the project. In the European context, the Norwegian approach on BVP is based on the Dutch version (Högnason et al 2018).…”
Section: Theoretical Background Lean and Bvpmentioning
confidence: 99%